Pengaruh Penggunaan Media Sosial Terhadap Prestasi Belajar Siswa Kelas V SD - Siti Ferda Harianti; Ragil Aria Dewanto; Rahmiati Rahmiati; Aries Suharso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of using social media on learning achievement in fifth grade students at SDN Kaliabang Tengah VIII Bekasi. This research was conducted in the even semester of the 2021/2022 academic year. The research method used is quantitative correlation. The instrument used for data collection is a questionnaire in the form of a statement in the form of a Likert scale for the use of social media and the average value of student report cards in the even semester of the 2021/2022 academic year for learning achievement. The results of the research, namely the calculation of the Normality test using Kolmogrof Smirnov, showed a significance value greater than 0.05, namely 0.200 > 0.05, then the sample data was normally distributed. And the Linearity test using the Simple Linear Regression test obtained a significant value of 0.000 < 0.05, it is concluded that the data sample is linearly distributed or related. In testing the hypothesis used Product Moment correlation test with a significant level of 0.05 obtained r table = 0.444. Significance is usually seen in the results of Sig. (2-tailed) the value = 0.000 < 0.05 and the correlation magnitude (r) 0.444 > 0.254 is greater than rtable, meaning that the correlation or relationship between the two variables is significant at the 0.05 level and can be seen from the number of the correlation coefficient. So Ha is accepted and Ho is rejected. The conclusion of this study states that there is a significant influence between the use of social media and the learning achievement of fifth graders at SDN Kaliabang Tengah VIII Bekasi.